2014
DOI: 10.1177/1362361314528390
|View full text |Cite
|
Sign up to set email alerts
|

Gestural communication in children with autism spectrum disorders during mother–child interaction

Abstract: Children with autism spectrum disorders display atypical development of gesture production, and gesture impairment is one of the determining factors of autism spectrum disorder diagnosis. Despite the obvious importance of this issue for children with autism spectrum disorder, the literature on gestures in autism is scarce and contradictory. The purpose of this study was to analyze gestural communication in children with autism spectrum disorder during spontaneous mother-child interaction. Participants were chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 50 publications
5
57
0
1
Order By: Relevance
“…Our results are consistent with prior findings of studies with preschool-aged children (e.g. Mastrogiuseppe et al, 2014;Medeiros and Winsler, 2014;Stone et al, 1997; but see Attwood et al, 1988;Capps et al, 1998).…”
Section: Gesture Frequency and Typessupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with prior findings of studies with preschool-aged children (e.g. Mastrogiuseppe et al, 2014;Medeiros and Winsler, 2014;Stone et al, 1997; but see Attwood et al, 1988;Capps et al, 1998).…”
Section: Gesture Frequency and Typessupporting
confidence: 93%
“…To our knowledge, no previous studies have addressed this issue in school-aged children. More importantly, most of these studies did not administer cognitive tasks in order to examine children's cognitive abilities (but see Mastrogiuseppe et al, 2014). Among various cognitive abilities, previous research has shown that verbal and spatial memories are associated with gesture frequency among normal individuals (Chu et al, 2014;Hostetter and Alibali, 2007;Sassenberg et al, 2011).…”
Section: Gesture Development In Children With Autism Spectrum Disordersmentioning
confidence: 99%
“…Importantly, the onset of such deictic gestures predicts the onset of similar spoken words in typically developing (TD) children (Iverson & Goldin-Meadow, 2005). Children with autism spectrum disorder (ASD) show difficulties in early gesture use, particularly in the production of deictic gestures (e.g., Mastrogiuseppe, Capirci, Cuva, & Venuti, 2015; Mundy, Sigman, & Kasari, 1990; Gulsrud, Hellemann, Freeman, & Kasari, 2014); they also often show prolonged delays in producing words and use fewer words than TD children (Tager-Flusberg, 2007). In this study, we ask how the delays and difficulties in the vocabulary development of children with ASD are related to different gesture types (deictic, give, conventional, iconic) produced in different communicative contexts (commenting, requesting).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we have shown that a cycle of twenty sessions of IMT is enough for a child with ASD to have a gain in synchrony and social engagement. Moreover, we have shown that to be high-functioning helps in the adaptation and in the learning of abilities (Mastrogiuseppe, Capirci, Cuva, & Venuti, 2015;Venuti & Bentenuto, 2015;Quintin et al, 2011), so we could suggest this type of therapy as particularly useful for this subtype of patients with ASD.…”
Section: Discussionmentioning
confidence: 97%